IMPLEMENTASI KOMPETENSI LEADERSHIP SKILL KEPALA MADRASAH DALAM MENINGKATKAN SINERGITAS KINERJA GURU DI MAN 3 ACEH UTARA - Fakhrizal, Fakhrizal; Muhajir, Al; Yuliza, Yuliza (Jurnal Sosial Humaniora Sigli, 2024)
The leadership of madrasah principals plays a strategic role in creating a conducive academic environment and enhancing teacher performance synergy. This study aims to analyze the implementation of the leadership skill competence of madrasah principals in fostering teacher performance synergy at MAN 3 Aceh Utara, explore the strategies employed by the principal, and identify the challenges faced in this implementation process. This research employs a qualitative descriptive method with data collection techniques including in-depth interviews, participatory observation, and document analysis. The findings indicate that the madrasah principal possesses strong leadership skills, which contribute to increasing teacher motivation, fostering collaboration among teaching staff, improving the quality of teaching, and strengthening teacher professionalism. Key strategies implemented include systematic academic supervision, teacher professional development programs, and strengthening partnerships with external stakeholders. However, several challenges exist in implementing leadership, such as a lack of leadership training for madrasah principals, limited resources, and differences in perspectives between the principal and educators in interpreting the madrasah’s vision and mission. The implications of this study emphasize that to enhance the effectiveness of madrasah principal leadership, there is a need for strengthened competency-based leadership training, a more systematic teacher performance evaluation system, and expanded strategic partnerships with various stakeholders. With the right strategies, the implementation of the leadership skill competence of madrasah principals can be further optimized to enhance teacher performance synergy and educational quality at MAN 3 Aceh Utara